Technology Clubs and Growth Patterns: Evidence from EU Manufacturing - Jaap W.B. Bos; Claire Economidou; M. Koetter (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2008)
This paper investigates the forces driving output change in a panel of EU manufacturing industries. A flexible modeling strategy is adopted that accounts for (i) inefficient use of resources, and (ii) differences in the production technology across industries. With our model we are able to identify technical, efficiency, and input growth for endogenously determined technology clubs. Both the technology clubs and the parameters within each club are modeled as a function of R&D intensity. This framework allows us to explore the components of output growth in each club, potential technology spillovers and catch-up issues across industries and countries.
Keywords: 330; growth; efficiency; R&D; stochastic frontier analysis; latent class